PROTECTION OF THE CONSTITUTIONAL ORDER AND SAFETY OF THE REPUBLIC OF SERBIA AGAINST DESTRUCTIVE AND DEVIANT BEHAVIORS (Heritage, 2024)
The importance of the defense of the Constitution and the state, in the structure, arrangement and size, as established by the act of the highest legal force, is invaluable from the aspect of the Republic of Serbia as a state that is under the attack of various destabilizing factors, either internal or external. The authors, with the work conceived in this way, first of all wanted to remind the general public, experts and laymen, of the determinants of the Constitution of the Republic of Serbia regarding the territorial integrity, territorial sovereignty, independence and constitutional arrangement, on the one hand, but also practices and illegal behaviors, which are potentially or truly aimed precisely at the destruction of the mentioned concepts. The goal of the work is a scientific and professional analysis and explanation of problems that arise at the internal or international level, and directly concern the stability of the constitutional arrangement of the Republic of Serbia. Recognizing the protection of the constitutional order of the Republic of Serbia as a delicate problem, the authors performed a legal-criminological-sociological analysis of the subject problem and analyzed the number of reported, accused and convicted persons for criminal acts aimed at the constitutional order and safety in the previous ten-year period. The purpose of the work is a causal analysis of criminal acts from this area with the aim of establishing possible improvements in the constitutional-legal or criminal-legal regulation, all with the aim of improving the protective or defense system of the Republic of Serbia.
Keywords: constitutional arrangement, safety, criminal acts against the constitutional arrangement